Identification of non-volatile components and anti-fatigue effect of a compound Lujiu - CHEN Ying, ZHU Yuzhe, YU Meili, LIU Fangmei, LI Cunyu, ZHENG Yunfeng, PENG Guoping (Zhongguo niangzao)
The non-volatile compounds in a compound Lujiu (38%vol) was detected by high-performance liquid chromatography quadrupole time-of- flight tandem mass spectrometry (HPLC-Q-TOF-MS/MS). The compound Lujiu was intragastric administered to mice for 22 d to investigate its effect on weight-bearing swimming and evaluate its anti-fatigue health benefits. The results showed that a total of 52 non-volatile substances were identified from the compound Lujiu (0.225 7 g crude drug/ml), including 24 saponins, 6 flavonoids, 4 nucleosides, 4 amino acids, 3 alkaloids, and 11 others. Compared with the model group, the body weight reduction of mice in the low, medium and high dose groups was significantly reduced (P<0.01), the weight-bearing swimming time of mice in the medium and high dose groups was significantly prolonged (P<0.01), the content of blood urea nitrogen (BUN) of mice in low and medium dose groups was significantly increased (P<0.01, P<0.05), the activity of lactate dehydrogenase (LDH) and the content of liver glycogen (LG) of mice in the low, medium and high dose groups were significantly increased (P<0.01, P<0.05), indicating that the compound Lujiu was rich in non-volatile substances, which could enhance the body's adaptability to load and had a significant anti-fatigue effect, providing a certain foundation for the development of functional foods.